Self-confidence and its Relationship with the Development of English Oral Communication Competence - Puli Quito, Fanny Elizabeth (2023)
The development of oral communicative competence has significantly been within the educational context. It is the main objective of pedagogical practice because it integrates cognitive and meta-cognitive skills and develops critical thinking skills. However, there are some barriers, in this case, the affective domains, specifically self-confidence, which intervene in oral practices within the class. Based on this, the purpose of this research was to observe, analyze and describe the relationship between a type of confidence-inducing stimulus, academic and the development of oral communicative competence in English of Sixth Year Basic General Education students of "Capullitos" School located in the City of Riobamba. The research took place under the qualitative approach with a descriptive case scope. For this, it was on the participation of twenty-eight students, and of course, the English teacher was also the fundamental participant. For data gathering, observation was used as a technique and the observation sheet as an instrument. The results indicate a significant correlation between self-confidence and oral proficiency in English during daily academic performance